2006
DOI: 10.1158/0008-5472.can-05-2881
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor ZEB1 Is Aberrantly Expressed in Aggressive Uterine Cancers

Abstract: The transcription factor ZEB1 (DEF1 in mice) has been implicated in cellular processes during development and tumor progression including epithelial to mesenchymal transition. DEF1 null mice die at birth, but heterozygotes expressing a LacZ reporter inserted into the DEF1 gene live and reproduce. Using these mice, we observed ZEB1 promoter activity in the virgin myometrium, and stroma and myometrium of the pregnant uterus. ZEB1 protein is up-regulated in the myometrium and endometrial stroma after progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
135
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 38 publications
6
135
0
1
Order By: Relevance
“…There was also epithelial ZEB1 expression in 4 and 5 out of 12 endometrial serous carcinomas and 29 carcinosarcomas, respectively. 26 A larger study (88 endometrial carcinomas) from the same group included a expanded number of endometrioid endometrial carcinomas (71 grade 1/2 and 17 grade 3), but also 3 undifferentiated endometrial carcinomas and 12 endometrial carcinomas with a serous component. ZEB1 expression was only observed in three grade 3 endometrioid endometrial carcinomas, 27 although it was not specified whether the ZEB1-positive grade 3 endometrioid tumors were the same in the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…There was also epithelial ZEB1 expression in 4 and 5 out of 12 endometrial serous carcinomas and 29 carcinosarcomas, respectively. 26 A larger study (88 endometrial carcinomas) from the same group included a expanded number of endometrioid endometrial carcinomas (71 grade 1/2 and 17 grade 3), but also 3 undifferentiated endometrial carcinomas and 12 endometrial carcinomas with a serous component. ZEB1 expression was only observed in three grade 3 endometrioid endometrial carcinomas, 27 although it was not specified whether the ZEB1-positive grade 3 endometrioid tumors were the same in the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…showed that PI(3) kinase contributes to TrkB signaling as well (including anoikis resistance; Douma et al, 2004), in aggregate these data suggest a model in which TrkB activates multiple pathways, some of which critically depend on Zeb1 (Figure 7). Several reports have shown a correlation between Zeb1 expression and the aggressiveness of tumors, including those of endometrial (Spoelstra et al, 2006;Singh et al, 2008), colon (Pena et al, 2005;Aigner et al, 2007b), breast (Aigner et al, 2007a), lung (Dohadwala et al, 2006), gallbladder (Adachi et al, 2009), ovarian (Bendoraite et al, 2010) and prostate origin (Graham et al, 2008). In colon cancer, Zeb1 expression is linked to loss of the basement membrane, which correlates with increased metastasis (Spaderna et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…41 Recently, several transcription factors that are molecular mediators of epithelial-to-mesenchymal transition, such as Twist, ZEB1, and HOXA10, have been shown to be expressed in endometrial carcinoma. 8,42,43 Of particular interest is that ZEB1 has an expression pattern in endometrial carcinoma quite similar to that for S100A4. None of these transcription factors has been shown previously to directly regulate S100A4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented interesting molecular differences between endometrioid and nonendometrioid endometrial carcinomas. [5][6][7][8] Metastatic or recurrent endometrial carcinomas represent a significant treatment problem, as current chemotherapeutic and hormonal strategies are entirely ineffective. Our laboratory has a long-term goal of identifying novel molecular events important in advanced endometrial carcinoma, with the ultimate goal of designing rational, targeted therapies for extra-uterine disease.…”
mentioning
confidence: 99%